Pengaruh Motivasi dan Insentif Terhadap Semangat Kerja Karyawan pada CU. Dosnitahi Pinangsori Kabupaten Tapanuli Tengah - Setianus Gulo; Yenni Sofiana Tambunan (EBISMA : Jurnal Ekonomi, Bisnis, Manajemen dan Akuntansi, 2026)
This study aims to determine the effect of motivation and incentives on employee work spirit at CU. Dosnitahi Pinangsori. This research uses a quantitative method with a descriptive correlational approach. The population consists of all active employees of CU. Dosnitahi Pinangsori totaling 66 people, and the sampling technique used is a census method. Data were collected through questionnaires using a Likert scale. The results show that partially, motivation has a positive and significant effect on employee work spirit with a significance value of 0.000 < 0.05. Incentives also have a positive and significant effect on employee work spirit with a significance value of 0.026 < 0.05. Simultaneously, motivation and incentives have a positive and significant effect on employee work spirit with a significance value of 0.009 < 0.05. These findings indicate that improving motivation and providing appropriate incentives can effectively enhance employee work spirit.